Protein Content and Organoleptic Test Central Sulawesi Pumpkin Seed Tempeh (Cucurbita moschata) for Learning Resource - Raodatul Jannah; Tri Santoso; Sri H. V. Pulukadang; Dewi S. Ahmar (Universitas Tadulako, 2025)
The yellow pumpkin (Cucurbita moschata) is a plant that readily adapts to diverse soil conditions; however, the utilization of its seeds remains restricted. Despite possessing a relatively high protein content crucial for growth and energy, it can serve as an alternative raw material for tempeh production. This study intends to generate yellow pumpkin seed tempeh in compliance with SNI 3144:2015 organoleptically, assess variations in the protein content of yellow pumpkin seed tempeh from three distinct regions in Central Sulawesi, and produce a Student Worksheet as an alternative resource for chemistry education through expert lecturer validation. This research employs a quantitative methodology utilizing the Kjeldahl analysis technique to ascertain protein concentrations across three phases: destruction, distillation, and titration. Furthermore, a sensory evaluation was conducted by 20 panelists to analyze the texture, color, flavor, and scent of yellow pumpkin seed tempeh. The resultant tempeh has favorable organoleptic properties, achieving an average preference score of 4, characterized by uniform white coloration, a distinctive tempeh aroma, and a dense texture. Protein content research revealed that tempeh from Palu City had the most significant protein concentration at 24.5 %, followed by Palolo District at 23.91 %, and North Lore District at 20.41 %, suggesting the impact of environmental factors on the nutritional composition of the manufactured tempeh. According to SNI 3144:2015, the visual characteristics of yellow pumpkin seed tempeh and its protein content conform to the established quality criteria. The findings of this study were presented as Student worksheets, which achieved a validity rate of 85 %, indicating its high suitability as a learning resource. This research enhances the application of yellow pumpkin seeds as a nutritious food source and fosters the creation of engaging and novel educational materials.